Social and Educational Problems Facing Hard of Hearing Students from the Schools' Teachers point of view " A Field Study in basic education schools in Lattakia city " - الرفاعي, عالية; الحواط, سلاف (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research aim to investigate the social and educational problems facing hard of hearing students from the schools' teachers point of view in basic education schools in Lattakia city, as well as the knowledge of the differences between the teachers in their awareness of the problems depending on the variables (sex, scientific qualification, years of experience), and to check for the aims of research used the descriptive method, was a questionnaire prepared problems hard of hearing, also studied their psychometric properties, and formed the sample of (234) teachers, for the academic year 2019/2020. The researcher reached several results, the most important of which is: Hard of Hearing Students suffer from social and educational problems to a high degree from the teachers' point of view. There are found in the teachers viewpoint about the social and educational problems suffered by students with hard of hearing according to the variable of sex, in favor of the female. There are no differences in the teachers viewpoint about the social and educational problems suffered by students with hard of hearing according to the variables of scientific qualification, years of experience. Based on results the of the research, the researcher presented the following suggestions: Attention to social and educational problems, which facing hard of hearing students, and work to stop it, also educating parents about these problems, their causes, and methods of treatment. working another research about social and educational problems facing hard of hearing students from the parents point of view, and compare the results with current research.